Proporsi Cokelat dan Rice Crispy-Mete sebagai Topping Terhadap Mutu Sensoris Crunchy Cake Gluten-free - Farah Musyafa'ah; Any Sutiadiningsih; Lilis Sulandari; Mafisa Restami (JURNAL ILMIAH NUSANTARA, 2026)
This study aimed to determine the sensory quality of gluten-free crunchy cake based on the proportion of chocolate and rice crispy-cashew as toppings. The study employed an experimental method with a quantitative approach. The pre-experimental stage involved nine trained panelists and was analyzed using the Friedman test followed by the Wilcoxon test. The results showed that the proportion of rice crispy and oven-roasted cashew nuts significantly affected the taste, texture, and overall liking attributes (p<0.05). The formulation containing 40% rice crispy and 60% oven-roasted cashew nuts obtained the highest mean rank scores for taste (2.67), texture (2.56), and overall liking (2.61), and was therefore selected as the best formulation for use in the main experiment. The main experiment was conducted using three proportions of chocolate and rice crispy-cashew toppings, namely 60%:40%, 70%:30%, and 80%:20%. Sensory evaluation was carried out by 35 trained and semi-trained panelists using a 5-point hedonic quality scale. The data were analyzed using One-Way ANOVA followed by Duncan’s Multiple Range Test (DMRT) at a 5% significance level. The results indicated that the proportion of chocolate and rice crispy-cashew significantly affected taste, texture, and overall liking (p<0.05). The formulation containing 80% chocolate and 20% rice crispy-cashew achieved the highest scores for taste (3.89), texture (3.91), and overall liking (4.14), and was therefore determined as the best formulation.